How responsible leadership shapes followers’ low-carbon behavior: A dual-mediation model - Zhang, Yihua; Liu, Xiyao; Zhang, Xiaoyan (Frontiers in Psychology, 2023)
In recent years, environmental problems such as global warming, rising sea levels, and species extinction have provoked a widespread concern all over the world, and many counties and international organizations have called for a reduction in carbon emissions. Theoretically, although many scholars have explored how responsible leadership influences subordinates’ work-related outcomes, little studies have examined the association between responsible leadership and employees’ low-carbon behavior. Therefore, to address this literature gap, we here drawing upon social cognitive theory developed a dual-mediation model to investigate how responsible leadership impacts employees’ low-carbon behavior, and through which mechanisms this impact may occur. By conducting a questionnaire survey in a company in China, we collected the valid data from 411 samples. Then using SPSS 26.0 and Mplus 8.1, we tested our proposed theoretical model and hypotheses by analyzing these data. The empirical results showed that responsible leadership was positively related to employees’ environmental consciousness, which further can increase their low-carbon behavior. At the same time, responsible leadership was negatively related to employees’ environmental apathy, which can reduce their low-carbon behavior. And employees’ environmental consciousness and environmental apathy played the mediating role in the relationship between responsible leadership and employees’ low-carbon behavior. Furthermore, we found that leader-member exchange (LMX) magnified the direct effect of responsible leadership on employees’ environmental apathy and strengthened the indirect effect of responsible leadership on employees’ low-carbon behavior via environmental apathy, but the moderating effect of LMX on another path was not significant. These findings suggest that despite encouraging leaders to show responsible behaviors, promoting employees’ environmental consciousness and reducing their environmental apathy may be useful ways to facilitating their low-carbon behavior and achieving a low-carbon society. Moreover, establishing a high-quality of exchange relationship with followers may magnify the effectiveness of responsible leadership on lowering followers’ environmental apathy.